(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article examined the femininity of Calixthe Beyala in "La Sonnette" through the prism of feminism, which is the social, economic, political, and cultural movement for gender equality. Femininity was created by Beyala to represent the unique suffering of African women; thus, femininity is a uniquely African philosophy. Although there are many types of feminism, the author has focused on the radical variety because of its close relationship to Calixthe Beyala’s femininity. Calixthe Beyala wants all women to have fun. Beyala examined the marginalisation of women on the African continent using her conception of feminism. She draws inspiration from her childhood and her experiences as an African woman to describe the painful situation of the African woman. She noted that in Western society, certain measures are taken for the emancipation of women, while in Africa, women are at the mercy of men. According to Calixthe Beyala, the development of patriarchy has reinforced the process of marginalisation of women in Africa. In her novels, Calixthe Beyala uses femininity to liberate women from male domination and oppression. In the novel, Beyala criticises the dress and demeanour of a typical African woman who lives to please the man. She wants women to have the same complete freedom as men, allowing them to have as many sexual partners as they want. In traditional African society, Beyala holds that a woman can also possess a man and use him as she sees fit. The title of the novel, La Sonnette has great importance in contemporary African society. The Bell symbolises the male domination suffered by African women and the oppression that accompanies this domination. The novel was written to alter the narrative of African society in which men dominated all aspects of women’s lives.